2017
DOI: 10.1021/acs.inorgchem.6b02792
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Ba3Nb2O8 Revisited: A Neutron Diffraction and Solid-State NMR Study

Abstract: ABSTRACT:The structure of Ba3Nb2O8 has been investigated using high resolution neutron powder diffraction. Our results show that whilst the structure has some features in common with the 9R perovskite and palmierite structures, it is a new and distinct structure. It is shown to follow a (chh)(hhc)(chh) sequence with BaO3- packing layers and is a cation and aniondeficient 9H perovskite polytype. Nb atoms occupy octahedral sites with vacancies between hexagonal close-packed layers. Isolated, corner-sharing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Preliminary refinement of the crystal structures from high-resolution X-ray diffraction (see Figure S10 and Table S2) showed that A 3 V 2 O 8 crystallizes with the palmierite structure (space group R 3̅ m ), which is composed by layers of isolated VO 4 tetrahedral units spaced by empty cationic vacancies. X-ray difference Fourier maps confirmed that V occupies only the 6 c Wyckoff site and that the vacancies are ordered (Figure S11), in contrast with what was seen in some hybrid hexagonal perovskite–palmierite Ba 3 M ′ M ″O 8.5 ( M ′ = Nb; M ″ = Mo, W) materials, where the cation vacancies are disordered. ,,, Previous neutron diffraction studies have shown that materials reported to have the palmierite structure can have more complex oxygen ordering, leading to the formation of hexagonal polytype structures with face- or corner-sharing octahedral units, e.g., Ba 3 Nb 2 O 8 . For this reason, neutron diffraction, which is more sensitive to the oxygen sublattice, was performed on the High-Resolution Powder Diffractometer (HRPD) at the ISIS Neutron and Muon Source at room temperature .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Preliminary refinement of the crystal structures from high-resolution X-ray diffraction (see Figure S10 and Table S2) showed that A 3 V 2 O 8 crystallizes with the palmierite structure (space group R 3̅ m ), which is composed by layers of isolated VO 4 tetrahedral units spaced by empty cationic vacancies. X-ray difference Fourier maps confirmed that V occupies only the 6 c Wyckoff site and that the vacancies are ordered (Figure S11), in contrast with what was seen in some hybrid hexagonal perovskite–palmierite Ba 3 M ′ M ″O 8.5 ( M ′ = Nb; M ″ = Mo, W) materials, where the cation vacancies are disordered. ,,, Previous neutron diffraction studies have shown that materials reported to have the palmierite structure can have more complex oxygen ordering, leading to the formation of hexagonal polytype structures with face- or corner-sharing octahedral units, e.g., Ba 3 Nb 2 O 8 . For this reason, neutron diffraction, which is more sensitive to the oxygen sublattice, was performed on the High-Resolution Powder Diffractometer (HRPD) at the ISIS Neutron and Muon Source at room temperature .…”
Section: Resultsmentioning
confidence: 85%
“…38,39,56,57 Previous neutron diffraction studies have shown that materials reported to have the palmierite structure can have more complex oxygen ordering, leading to the formation of hexagonal polytype structures with face-or corner-sharing octahedral units, e.g., Ba 3 Nb 2 O 8 . 58 For this reason, neutron diffraction, which is more sensitive to the oxygen sublattice, was performed on the High-Resolution Powder Diffractometer (HRPD) at the ISIS Neutron and Muon Source at room temperature. 59 Refinement of the crystal structures from neutron diffraction data resulted in an excellent fit to the data (see Figure S12 and Table S3), thus confirming that A 3 V 2 O 8 (A = Sr, Ba) indeed crystallize in the palmierite structure with layers of isolated tetrahedral units (Figure 4a,b).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Overall, our findings demonstrate that water absorption and high ionic mobility are promoted in Ba 7 Nb 4 MoO 20 thanks to the ability of the crystal lattice of accommodating anion and cation disordered environments and to the dynamic and rotational flexibility of the oxygen-deficient palmierite layers. The example of Ba 7 Nb 4 MoO 20 suggests that candidate materials with cation deficient layers or palmierite-like motifs in the vast family of hexagonal perovskite derivatives are likely to support significant oxide ion and/or proton conduction. , Importantly, the insights presented here demonstrate that fast proton conduction can be enabled by disordered solid oxide systems (in contrast with conventional cubic perovskite conductors where ionic transport is promoted by the high symmetry of the crystal lattice) and provides innovative design rules for the development of solid electrolytes crystallizing in oxides with disordered sublattices.…”
Section: Discussionmentioning
confidence: 92%
“…Previous neutron diffraction studies have shown that materials reported to have the palmierite structure can have more complex oxygen ordering leading to the formation of hexagonal polytype structures with face-or corner-sharing octahedral units, e.g. Ba3Nb2O8 58 . For this reason, neutron diffraction, which is more sensitive to the oxygen sub-lattice, was performed on the High Resolution Powder Diffractometer (HRPD) at the ISIS Neutron and Muon Source at room temperature 59 .…”
Section: Figure 3 Arrhenius Plot Of the Bulk Proton Conductivity Ofmentioning
confidence: 99%